Avaliação do projeto atleta do futuro (PAF/CHAPECÓ) sob a ótica da sociologia reflexiva de Pierre Bourdieu - Johann, Mauro Luiz (2018)
Supported by the studies of the sociologist Pierre Bourdieu, that go beyond the Social Sciences, therefore his work fundaments many themes, including the sport, we performed the Evaluation of the Projeto Atleta do Futuro Cidadão (PAF). This project, as a public policy created and implemented based in constitutional rules of the Brazilian State, has been functioning since 2007 in the city of Chapecó (SC). PAF happens in a specific social background, according to its guidelines it aims to promote educational sports practices to children and adolescents, among its goals is the incorporation of values led by formal and non-formal education. Taking this approach into consideration and having PAF as object of investigation, the present study proposes to evaluate the Projeto Atleta do Futuro under the vision of the reflexive sociology of Bourdieu, drawing a parallel between its foundations, its possibility of existence and of the conditions of offering the project to participants, so they may expose and stand for their interests concerning the sportive modalities they practice. Considering the tradition of Bourdieu’s sociology, reflecting questions over the sense of the social practice, the importance of evaluating PAF is centered in the search of understanding the degree of reach its actions have, when questioning what does PAF want? What do the participants of PAF desire? And what, indeed, PAF is offering. The methodological path follows the sociologic orientation of Bourdieu: “researching is a craft”. Nevertheless, without dismissing other research methods and technics, due to the study being a bibliographic and documental study, we employed the Content Analysis method envisioned by Laurence Bardin. The study is organized in the following order: the first chapter emphasizes the State and public policies targeted to the development of sportive educational projects. Subsequently, there is a reference to the reflexive sociology of Bourdieu and to the structures that compose the fields and subfields of sport. The organization of the study is explained in its methodological path, followed by the presentation of PAF, along with the context of its creation and conception. In the final chapter, the athlete, the teacher, PAF and the researcher gain voice in the title: In the attempt of comprehending why “researching is a craft”. Regarding the results, that were arranged and detailed based in statistical data catalogued in charts, it is expected, among others, that they don’t ignore the foundations and possibilities of existence of PAF, however, because of it, show a diagnostic of the conditions and practical actions the project offers to its participants and, that they expose and stand for their interests concerning the sportive modalities they practice. Key-words: Projeto Atleta do Futuro (PAF). Reflexive Sociology. Sport. Education.